Has a Fashion Instagram Poster Ads Has Its Linguistic Meaning? Multimodal Discourse Analysis Approach - Utami, Ria; Farid Agustian, Agung; Meilany Putri, Hillda (Talenta Publisher, 2023)
This research aimed to identify the visual elements of Uniqlo Indonesia Instagram Ads. The method of the study was the descriptive qualitative method. The techniques of collecting data in this research were literature study and documentation. The data sources were eight advertisements analyzed by the Visual Grammar Design Theory of Kress and Van Leeuwen (2006). The results showed that the Uniqlo Indonesia Instagram Ads implied representational, interactional, and compositional meanings. Representational, Narrative Representation includes of action process; non-transactional was more significant than transactional. Conceptual representation consists of an analytical process. For Interactional, the Participant was Represented than Interactive. The gaze system included Demand being higher than Offer. The social distance was Personal. The Close Social was more significant than the Far Social. The perspective had a Subjective image found in terms of High modality. While conveying a message, the ads were directed to attract the viewer